Thermoresponsive Polymer Nanoparticles Co-deliver RSV F Trimers with a TLR-7/8 Adjuvant - Francica, Joseph R; Lynn, Geoffrey M; Laga, Richard; Joyce, M Gordon; Ruckwardt, Tracy J; Morabito, Kaitlyn M; Chen, Man; Chaudhuri, Rajoshi; Zhang, Baoshan; Sastry, Mallika; Druz, Aliaksandr; Ko, Kiyoon; et al. (Bioconjugate chemistry, 2016)
Structure-based vaccine design has been used to develop immunogens that display conserved neutralization sites on pathogens such as HIV-1, respiratory syncytial virus (RSV), and influenza. Improving the immunogenicity of these designed immunogens with adjuvants will require formulations that do not alter protein antigenicity. Here, we show that nanoparticle-forming thermoresponsive polymers (TRP) allow for co-delivery of RSV fusion (F) protein trimers with Toll-like receptor 7 and 8 agonists (TLR-7/8a) to enhance protective immunity. Although primary amine conjugation of TLR-7/8a to F trimers severely disrupted the recognition of critical neutralizing epitopes, F trimers site-selectively coupled to TRP nanoparticles retained appropriate antigenicity and elicited high titers of prefusion-specific, TH1 isotype anti-RSV F antibodies following vaccination. Moreover, coupling F trimers to TRP delivering TLR-7/8a resulted in ∼3-fold higher binding and neutralizing antibody titers than soluble F trimers admixed with TLR-7/8a and conferred protection from intranasal RSV challenge. Overall, these data show that TRP nanoparticles may provide a broadly applicable platform for eliciting neutralizing antibodies to structure-dependent epitopes on RSV, influenza, HIV-1, or other pathogens.
Keywords: syntetické vakcíny; neutralizující protilátky; Vaccines, Synthetic; toll-like receptor 8; Respiratory Syncytial Virus Vaccines; Nanoparticles; Toll-Like Receptor 8; nanočástice; Toll-Like Receptor 7; Polymers; toll-like receptor 7; Adjuvants, Immunologic; Drug Delivery Systems; Animals; techniky syntetické chemie; ženské pohlaví; polymery; Viral Fusion Proteins; proteiny virové fúze; adjuvancia imunologická; zvířata; Antibodies, Neutralizing; inbrední kmeny myší; Chemistry Techniques, Synthetic; Female; vakcíny proti respiračnímu syncyciálnímu viru; Mice, Inbred Strains; lékové transportní systémy